(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This work presents new strategies of teaching tourism terms as an adaptive system in language teaching classrooms. The basic reason for learning tourism terms that all people have in common is communication - communication in any mode. It is a two-sided process, which requires the ability to understand each other, to be able to code a message that someone wants to convey to someone else in a way, which will be comprehensible to the receiver and also appropriate to a concrete situation and status of all participants. To adapt means to make or undergo modifications in function and structure so as to be fit for a new use, a new environment or a new situation. The adaptive system approach to tourism terms is still in its infancy, but it is already possible to hazard an interim estimate of its significance